Development and design of 3D virtual laboratory for chemistry subject based on constructivism-cognitivism-contextual approach - Bakar, Norasiken; Badioze Zaman, Halimah (Springer-Verlag Berlin Heidelberg, 2006)
This paper address about designing virtual laboratory for chemistry subject, acid, base and salt (VLab-CHEM) in three dimension (3D). Discussion involved on theoretical framework modelling where it divided into two parts that is analysis, design, development and evaluation. For the second objective, researcher was view on constructivism-cognitivism-contextual lifecycle model where it used for 3D VLab-CHEM. This model defined about education media, how to measure content, authoring program and systematic instructional design. For the third objective, researcher also explained the 3D laboratory architecture and storyboard for the early state of development VLab-CHEM. Others objective are defining Instructional Design (ID) model (VLab-CHEM) where it include 3D virtual laboratory modules. ID model focused on learning and teaching aspects and science education, education process and by using multimedia interactive module. While designing the development of VLab-CHEM, researcher has used approach in learning theory such as constructivism-cognitivism-contextual. Concept through learning-by-doing, contextual education, simulation, 3D animation and real time animation to create 3D virtual based on reality, added in the VLab-CHEM.